2021
DOI: 10.1007/s13139-020-00674-3
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Need for Adjusting 131I Activity for the Treatment of High Turnover Graves’ Disease Compared to Normal Turnover Patients? Results from a Retrospective Cohort Study Validated by Propensity Score Analysis

Abstract: Purpose To compare 131 I-therapy outcomes in high turnover and normal turnover Graves' disease patients and predict optimal first 131 I activity for high turnover patients. Methods Retrospective cohort design (1:2) validated by propensity score analysis. Cohort 1, high turnover (2-h RAIU/24-h RAIU ≥ 1), n = 104, and cohort 2, normal turnover (ratio < 1), n = 208, patients were compared for post 131 I outcome. The cure was defined as a combined euthyroid and stable hypothyroid state following 131 I treatment. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Our results further strengthened the outcome of retrospective analysis by Kuanrakcharoen that indicated a 66.3% success rate of I-131 treatment at 1 year [51]. However, the current findings contradicted the results of a recent retrospective study by Arora et al that indicated a variable (i.e., 31-60%) success rate of RAI treatment [52].…”
Section: Discussionsupporting
confidence: 64%
“…Our results further strengthened the outcome of retrospective analysis by Kuanrakcharoen that indicated a 66.3% success rate of I-131 treatment at 1 year [51]. However, the current findings contradicted the results of a recent retrospective study by Arora et al that indicated a variable (i.e., 31-60%) success rate of RAI treatment [52].…”
Section: Discussionsupporting
confidence: 64%
“…Moreover it may be refined by estimating the thyroid gland size by palpation, morphological, or functional imaging (i.e., TUS or thyroid scintigraphy, respectively) (i.e., fixed administered activity per mass unit) [ 1 , 6 ]. In addition, Na[ 131 I]I thyroid gland maximum uptake and turnover should be empirically taken into account when therapeutic RAI activity is planned [ 88 ].…”
Section: Rai Therapy For Patients With Autoimmune Hyperthyroidism (Gr...mentioning
confidence: 99%